Hybridisation of perovskite nanocrystals with organic molecules for highly efficient liquid scintillators - Cho, Sangeun (Light Sci Appl, 2020)
Compared with solid scintillators, liquid scintillators have limited capability in dosimetry and radiography due to their relatively low light yields. Here, we report a new generation of highly efficient and low-cost liquid scintillators constructed by surface hybridisation of colloidal metal halide perovskite CsPbA(3) (A: Cl, Br, I) nanocrystals (NCs) with organic molecules (2,5-diphenyloxazole). The hybrid liquid scintillators, compared to state-of-the-art CsI and Gd(2)O(2)S, demonstrate markedly highly competitive radioluminescence quantum yields under X-ray irradiation typically employed in diagnosis and treatment. Experimental and theoretical analyses suggest that the enhanced quantum yield is associated with X-ray photon-induced charge transfer from the organic molecules to the NCs. High-resolution X-ray imaging is demonstrated using a hybrid CsPbBr(3) NC-based liquid scintillator. The novel X-ray scintillation mechanism in our hybrid scintillators could be extended to enhance the quantum yield of various types of scintillators, enabling low-dose radiation detection in various fields, including fundamental science and imaging.